Percutaneous absorption and toxicological risks in the newborn infant. - Wepierre, J. (European Journal of Pediatric Dermatology, 2018)
The susceptibility of full term and preterm newborn infants to the systemic and sometimes toxic side effects of topically applied drugs or some hygienic products is higher than in adults. This is partly explained by considering that the skin of preterm baby is much more permeable of that of the adult. On the other hand, it does not exist any difference of permeability between the skin of the full term newborn infant and that of the adult, but other factors should be taken into account. First, the surface/body weight rate is much higher in the newborn as compared with the adult. This leads in the newborn to very high plasmatic concentrations the absorbed substances being equal. Moreover, the biological half-life of foreign substances is longer in the newborn as compared with the adult, due to the immaturity of catabolism and elimination processes. Lastly, the conditions of usage (occlusion, large surfaces, eroded skin) favor a more massive absorption in the baby infant. Examples of these different factors are discussed.